2013
DOI: 10.1007/s00705-013-1737-0
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma outbreak in a GASH:Sal hamster colony

Abstract: We have detected a high incidence of lymphomas in a colony of GASH:Sal Syrian golden hamsters (Mesocricetus auratus). This strain is characterised by its ability to present convulsive crises of audiogenic origin. Almost 16 % (90 males and 60 females) of the 975 animals were affected during a 5-year period by the development of a progressing lymphoid tumour and exhibited similar clinical profiles characterised by lethargy, anorexia, evident abdominal distension, and a rapid disease progression resulting in mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The insertion of four nucleotides in noncoding region between LTag and VP1 genes in BVPyV (KS/13/999) genome was also determined. This is in line with previous studies indicating that the highest level of variation is common for noncoding regions of PyVs [ 73 , 75 ].…”
Section: Resultssupporting
confidence: 93%
“…The insertion of four nucleotides in noncoding region between LTag and VP1 genes in BVPyV (KS/13/999) genome was also determined. This is in line with previous studies indicating that the highest level of variation is common for noncoding regions of PyVs [ 73 , 75 ].…”
Section: Resultssupporting
confidence: 93%
“…For production of HPyV12-derived VP1 VLPs in yeast, we used both the native virus gene sequence (HPyV12 VP1n 380 ) and a version that was codon-optimized for S. cerevisiae expression (HPyV12 VP1s 380 ), synthesized by GenScript. Both VP1-encoding genes were cloned into the expression vector, pFX7 [ 25 ], and transformed into the yeast strain, AH22-214. Expression of HPyV12 VP1 380 , analyzed using SDS-PAGE, was low using both versions of the gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MCPyV has gained the most attention due to its link with a rare and aggressive malignant human skin cancer, Merkel cell carcinoma, in the elderly and chronically immunosuppressed individuals [ 19 ]. It has been shown that hamster polyomavirus (HaPyV) is responsible for the high incidence of lymphomas in a colony of genetic audiogenic seizure hamsters (GASH:Sal) [ 25 ]. Moreover, proteins encoded by some PyVs have transforming ability in cell culture and tumorigenic activity in animals [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains possible that the apparently VP2-independent infectious route is also relevant to pathobiology. A recent publication from Muñoz and colleagues documents an outbreak of hamster polyomavirus (HaPyV)-induced lymphoma [59]. Interestingly, most HaPyV genomes isolated from lymphoma cells were found to have deletion mutations encompassing the N-terminus of VP2 and, in one instance the N-terminus of VP3 as well.…”
Section: Discussionmentioning
confidence: 99%